Integration of Youth: Ways of Perception and Understanding of "Others" - Čaldarević, Ognjen; Švob, Melita; Brčić, Carmen (2005)
Investigations about youth orientation (EU, national, regional)and their integration in society. Three focus group has been organized in primary and secondary schools in district Dubrava (Zagreb)with pupils of different national and social belonging.One focus group has been analysed in Jewish community Zagreb.
Projekt MZOS
ENG